Descripción unidad funcional lagrimal en trabajadores de placita de Flórez expuestos a contaminación, Medellín 2020 (2020)
Air pollution is the cause of multiple respiratory and cardiovascular diseases. There are different atmospheric pollutants. The World Health Organization (WHO) considers that the cause is Particulate Material (PM). This research project arises from the need to describe the changes that exist in the lacrimal functional unit due to contamination, this in workers who are constantly exposed in the center of the city of Medellín. This study was carried out between November 2019 and January 2020, describes the lacrimal functional unit of the workers of the Placita de Flórez de Medellín, who are exposed to variations in contamination as reported in the weekly indexes of the early warning system of Medellín and Valle de Aburrá (SIATA).